South African Nation Branding: A comparative study and the analysis of incidents that have affected the country’s nation brand during and post 2010 FIFA World Cup. - Gourlay, Kirsty Michelle (The IIE, 2016)
South Africa was successful in portraying a positive nation brand pre and during the 2010 FIFA World Cup, however certain social, political and economic incidents have led to a failing nation brand. South Africa proved itself to the world that they were capable in hosting a mega –sporting event and that the country possessed attractive opportunities to varying internal and external stakeholders. Post 2010 there has been varying incidents that have influenced ‘Brand South Africa’ and led to the decay of a once positive and progressive nation brand. It is thus imperative that we unpack and investigate these issues and varying influences in order to further understand the problem South Africa is currently facing with regards to nation branding and the ways in which it can be addressed and rectified. Experts in the field of nation branding have been sourced from Johannesburg, Cape Town and Durban as to further understand the concept of nation branding and what it means for a country and its stakeholders. Textual analyses have also been used to add further insight and to gain a deeper understanding into the research problem. Primary data consists of four individuals, where each participant was asked questions pertaining to South African nation branding, their thoughts, opinions and beliefs on the matter. All data was then gathered and analysed and findings were explored and discussed as to accurately ascertain what specific influences have caused the current state of ‘Brand South Africa’ and why. As a result of completing the above research, the researcher was able to confirm that the successes of South Africa being able to portray a positive nation brand was as a result of impeccable organisation and cohesive communication pre and during the mega sporting event in 2010. However what the researcher later discovered was that the root of South Africa’s failing nation brand post the 2010 FIFA World Cup was due to lack of communication from political organisations and internal South African stakeholders as well as incompetent leadership from varying political and social parties. Thus we can conclude that all South African stakeholders are responsible for the maintenance and successful portrayal of the country’s nation brand and that no one party or individual are solely to blame for the failing image of ‘Brand South Africa’ post 2010. This paper aims to further enlighten readers as to how South Africa is perceived as a nation brand and why. As a result of successfully identifying the specific influences that have led to the country’s current national state, it is the objective of this paper to enlighten and specifically encourage South African stakeholders in working towards successfully maintaining a positive nation brand.
Keywords: Nation branding